TELAAH BIAYA DAN PENERIMAAN DARI SUDUT PANDANG EKONOMI SYARIAH - Faisal Affandi (EKSYA : Jurnal Ekonomi Syariah, 2021)
In essence, sharia economics is the application of sharia in various micro and macro economics activities. Talking about microeconomics, it will be in direct contact with the main issues analyzed in microeconomics theory namely, “how to use the available factors of production efficiently so that the prosperity of the people can be maximized”. Production has an important role in determining the standard of human life and the welfare of a nation. The purpose of this study is to analyze how the comparison of costs and revenues is seen from the point of view of conventional economics and sharia economics. This research is a library research whose data is through library sources and other references related to the development of costs and revenues in terms of conventional economics and sharia economics. The results of this study indicate that, (1) production costs seen from the point of view of sharia economics are all costs originating from halal sources and incurred by companies to obtain production factors that will be used to produce goods or services, (2) revenue is the receipt of producers from the sale of their production, (3) producer are assumed to always choose the level of output at which they can get the maximum total profit, (4) at the same cost, the amount of production in the profit sharing system is greater than the amount of production in the interest system, (5) production cost in a profit sharing system are more efficient and are able to encourage producers to produce at larger economies of scale